Prospects for Energy Transition to Hydrogen Fuel: Analysis of World Experience and Russian Practice - Berezin, Andrey; Gorodnova, Natalia; Sergi, Bruno S.; Handoko, Chanel Tri; Permana, Chrisna T. (International Journal of Energy Economics and Policy, 2023)
A significant depletion of natural energy reserves and a sharp rise in its cost of production amidst a civilizational energy crisis, greenhouse gas issue, and increasing energy consumption have called for an urgent and radical change in the global energy agenda. An idea to promote hydrogen as an alternative energy emerges from the global energy transition agenda. In this article, our aim is to assess the prospect of hydrogen, as a potential, environmentally friendly, yet expensive and technological-demanding resource, to be developed globally. The scientific novelty of the research consists in systematizing the world experience and Russian practice of implementing energy efficiency projects within the framework of public-private partnership (PPP), substantiating, and forecasting the prospects for the use of this resource in order to decarbonize the economy and solve environmental problems, as well as determining the main directions of the national energy strategy in Russia. We have developed recommendations to eliminate the identified problems that impede the increase in the energy efficiency of industrial production and operation of facilities. It is concluded that the use of “green” hydrogen obtained with the help of renewable energy sources is promising in solving environmental problems and building a climate-neutral economy characterized by zero greenhouse gas emissions. The results of the work can be useful in well-supporting hydrogen ecosystem.